Taxation and Human Capital Development in Nigeria: A Dynamic Analysis using the Error Correction Model (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study empirically examined the impact taxation on the Human Development Index (HDI) in Nigeria, for the period 1990 - 2024. The error correction model was used to evaluate both short-run and long-run impact of the independent variables on the dependent variable. The results showed that Company Income Tax (CIT) and Petroleum Profit Tax (PPT) had a negative and significant impact on HDI in the short run, while Value Added Tax (VAT) demonstrated a positive and significant relationship. Customs and Excise Duties (CED) were found to negatively affect HDI, though insignificantly in the short run. In the long run, CIT continued to have a negative but insignificant impact, while PPT and CED maintained a negative and significant effect. VAT remained the only tax component with a consistently positive and significant influence on human development. Despite a confirmed long-run relationship between tax revenue and HDI, the study highlights that increasing tax revenue in Nigeria has not translated into significant human development gains, likely due to poor fiscal discipline, tax evasion, weak policy implementation, and lack of transparency. The findings recommended the need for tax policy reform, improved revenue utilization, and stricter enforcement to enhance the developmental impact of tax revenue in Nigeria.